The Modified THP-1 Activation Assay for the In Vitro Identification of Drug-Inducing Systemic Hypersensitivity - Iulini, Martina; Maddalon, Ambra; Galbiati, Valentina; Corsini, Emanuela (Frontiers in Toxicology, 2022)
The development of new low molecular weight drugs has many chances of failure and is an expensive process. Currently, there are no screening methods and/or models to assess the hazard of hypersensitivity reactions to drugs (DHRs) in the preclinical phase. DHRs represent 6–15% of adverse drug reactions. Although rare, DHRs represent a serious health problem for predisposed individuals, resulting, in some cases, in life-threatening pathologies. To date, there are no in vitro or in vivo sensitive models able to predict the sensitizing potential of drugs in the preclinical tests, and these reactions are highlighted only after the drug has been placed on the market, affecting both population and public health. This article describes a novel approach methodology for the study of the sensitizing potential of drugs based on the use of the human promyelocytic cell line THP-1 as a surrogate for dendritic cells. The method is based on the upregulation of specific surface markers (CD86 and CD54) and on the production of IL-8. In our experience, the THP-1 activation assay allowed the correct identification of drugs known to induce systemic hypersensitivity in humans, including the one associated with specific HLAs. This method may help to discover possible systemic hypersensitivity reactions early in the preclinical phase of drug development.